Keystone roles of carbon-degrading enzyme activities in mediating carbon in soils subjected to straw return: a global meta-analysis - Somchanh, Somdee; Li, Yue; Yang, Ling; Wei, Ran; Zhang, Yuxuan; Liu, Bing; Jiang, Qingwen; Yang, Qiliang (Frontiers in Microbiology, 2026)
IntroductionStraw return exerts a profound impact on soil fertility, with particularly critical implications for soil carbon (C) pools. Soil hydrolytic C-degrading extracellular enzyme activities (Hy-EEAs) play a central role in soil C cycling. However, the effects of straw return on Hy-EEAs, below-ground C dynamics, and the underlying regulatory mechanisms have not been fully elucidated.MethodsIn this study, we evaluated the effects of straw incorporation on Hy-EEAs and below-ground C, as well as their potential relationships, by synthesizing 211 observations from 68 published field studies worldwide.ResultsOn average, straw return significantly enhanced Hy-EEAs by 25% but had no effect on β-xylosidase. Straw return significantly increased dissolved organic carbon, easily oxidizable carbon, light fraction organic carbon, particulate organic carbon, microbial biomass carbon, and soil organic carbon by 27, 24, 51, 34, 31, and 20%, respectively, compared to the no-straw-return treatment. The effect of straw return on Hy-EEAs decreased with increasing experiment duration (≥ 10 years). Straw return effects on Hy-EEAs increased with the incorporation of straw. The response ratios (lnR) of microbial biomass C content and soil organic carbon (SOC) storage to straw return were positively correlated with the lnR of Hy-EEAs; however, no clear relationships were found between the lnR of soil dissolved organic C (DOC), easily oxidizable C (EOC), light fraction organic C (LFOC), and particulate organic C (POC) and the lnR of Hy-EEAs.DiscussionThese results suggest that straw return stimulation of Hy-EEAs exhibited a key role in regulating below-ground C dynamics. Future biogeochemistry models could incorporate the observed relationships in this study between the soil C pool and Hy-EEAs, which can improve model predictions of C in soils under straw return in agricultural systems.